Total phenolic contents and colour intensity of Malaysian honeys from the Apis spp. and Trigona spp. bees - Kek, Siok Peng; Chin, Nyuk Ling; Yusof, Yus Aniza; Tan, Sheau Wei; Chua, Lee Suan (Elsevier, 2014)
The total phenolic content and colour intensity of the five common Malaysian honeys by the Apis spp. or Trigona spp. were studied following a modified Folin-Ciocalteu method and absorbance measurements, respectively. The total phenolic content and the colour intensity of honeys from the two types of bees were statistically different with P < 0.0005. The Trigona spp. honey gave higher total phenolic content with average 784.3 mg GAE/kg than the Apis spp. honey at average 590.5 mg GAE/kg. The total phenolic content of Malaysian honeys has good correlation with its colour intensity at R2 = 0.826.